Idiosyncratic Shocks and Child Labor: Does Gender Matter? Evidence from Indonesia - Bayu Kharisma; Elan Satriawan; Lincolin Arsyad (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2017)
This paper aims to analyze the effect of various idiosyncratic shocks against child labor, working hours of children and school participation based on gender. Also, the role of the assets held by households as one of the coping strategies to mitigate the effects of such shocks. The results of random effect probit technique show that girls are more vulnerable and unprotected in the event of idiosyncratic shocks, especially those shocks caused by crop loss and the decline in household income due to price and quantity. Meanwhile, idiosyncratic shock that drives the existence of boys child labor is the death of the head or members of the household.. Additionally, household assets play an important role in reducing the number of child labor and increase school participation but do not affect the working hours of children during a variety of idiosyncratic shocks